Construção de uma máquina de solda a ponto por resistência de baixo custo - BARBOSA, Matheus dos Santos (2022)
The Electric resistance welding is used mainly in the joining of parts in the automobile body due to its high welding speed and the good final quality of the weld. This work aims to develop a low cost electrical resistance welding machine, analyzing the parameters involved in the process and applying the knowledge acquired during the mechanical engineering course, in order to make it available to course students to assimilate them didactic way the contents of the disciplines of the area of manufacturing processes. The project was carried out in a way to use materials of low cost, that were available in the laboratory of the Campus and at the same time to meet the necessary operational parameters. For the supply of the electric current, a microwave transformer was used and for the application of force a mechanical system with pedal. Then, samples of 0.5 mm thickness of carbon steel plates were welded and subjected to the pullout test, which was applied in a qualitative way, this is used to verify the dimensions of the weld point. To perform the validation of the parameters used AWS D8.7-88 of 1987 was consulted, according to it for the thickness used in the samples the diameter of the point should be around 3.0 mm while the average of the diameters measured in the samples was 2.54 mm, despite small variations it was possible to validate the established parameters.